Evaluation of the adhesive properties of vanillin-derived polyhydroxy urethanes - Ghuge, Gorakh Hiraman; Kambikanam, Karthika Vayalachery; Nair, Kiran Sukumaran (Journal of Applied Polymer Science, 2023)
Poly(hydroxy urethanes) (PHUs) have been considered attractive and safer variants of conventional polyurethanes (PUs). To improve the prerequisites of green and sustainable chemistry herein, we propose the synthesis and utilization of cyclic carbonate monomers majorly derived from vanillin, a lignin derivative, and CO2 for the development of PHUs. Kinetic evaluation on the polymerization temperature ascertained 80 degrees C as the optimum condition for PHU synthesis. The structural evaluation of PHUs was carried out by various spectroscopic techniques, such as FTIR, (HNMR)-H-1, and C-13-NMR, molar masses were determined by gel permeation chromatography (Mn varied between 2500 and 11,100 g/mol), and thermal properties evaluated by differential scanning calorimeter (Tg in the ranges of 28-42 degrees C), and thermogravimetric analysis (stable above 180 degrees C). Since the PHUs are enriched with pendant hydroxyl groups on their backbone which can promote adhesion, lap shear studies on the aluminum substrate exhibited a maximum shear strength of 1.65 +/- 0.37 MPa. This study demonstrates an attractive and environment-friendly pathway for developing novel PHUs network using renewable biobased resources and further explores its applicability as adhesives.
Keywords: adhesive; biobased cyclic dicarbonate; diamines; poly(hydroxyurethane)s; Vanillin

Synthesis and characterization of thermosetting adhesives from epoxidized Thevetia peruviana oil for sustainable bonding solutions - Kambikanam, Karthika Vayalachery; Bindu, Bhadra Purushothaman; Olosho, Adebayo Isaac; Nair, Kiran Sukumaran (RSC Sustainability, 2025)
<div class="abstract author" id="aep-abstract-id5" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> The demand for bio-based epoxy thermoset alternatives within the adhesive industry has seen substantial growth in recent years. This increase is attributed to a heightened exploration of renewable materials, including biopolymers and monomers derived from renewable resources. However, despite these significant advancements, a considerable portion of the research primarily focuses on edible oils, which may inadvertently neglect critical implications for food security. So, this study explores the thermal, mechanical, and adhesive properties of epoxy thermosets derived from biobased epoxidized Thevetia peruviana oil (ETPO) cured with two diamines, 1,10-decane diamine (DDA) and m-xylene diamine (XDA), using imidazole (IM) as a catalytic initiator. The thermosets were evaluated for lap shear strength on stainless steel (SS) and aluminium (Al) substrates at varying imidazole concentrations (0–5%) and curing times (24–96 hours). The results show that DDA-cured thermosets demonstrate superior thermal stability and heat resistance, with T5% increasing from 149 °C to 256 °C and THRI from 139 °C to 162 °C as IM concentration rises. XDA-cured thermosets exhibit higher adhesive strength, peaking at 1.47 MPa on SS at 5% IM and 72 hours, but lower thermal stability, with T5% values decreasing from 157 °C to 68 °C. Imidazole's catalytic efficiency enhanced the crosslinking in both systems, with DDA providing better thermal stability and XDA delivering higher adhesive strength. These findings demonstrate the potential of ETPO-based thermosets as sustainable adhesives, offering excellent performance for industrial applications. <div class="abstract graphical" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> The demand for bio-based epoxy thermoset alternatives within the adhesive industry has seen substantial growth in recent years.